2018
DOI: 10.1016/j.gie.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Boston Bowel Preparation Scale scores predict the risk of missed neoplasia on the next colonoscopy

Abstract: Inadequate BBPS segment scores generally are associated with higher rates of polyps and advanced polyps at subsequent colonoscopy within a short timeframe. The presence of advanced polyps as well as inadequate BBPS segment scores can inform the risk of missed polyps and help triage which patients warrant a timely repeat colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 26 publications
1
44
0
2
Order By: Relevance
“…Consistent with this conclusion, segmental scores of ≥ 2 predict a lower risk of polyps in that segment at follow up colonoscopy 36 .…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…Consistent with this conclusion, segmental scores of ≥ 2 predict a lower risk of polyps in that segment at follow up colonoscopy 36 .…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…Based on these findings, the investigators suggested that a total BBPS score of ≥ 6 and/or all segment scores ≥ 2 may serve as a standard definition of “adequate for 10-year follow-up”[ 44 ]. However, a prospective, observational study in a large, national endoscopic consortium found that inadequate single BBPS segment scores at the initial, average-risk screening colonoscopy were correlated with significantly greater risk of polyps at a second colonoscopy, suggesting that both a total score of ≥ 6 and all segment scores ≥ 2 should be required as an adequacy standard for 10-year follow-up[ 56 ]. This assessment was affirmed by a study in 438 colonoscopies in men, which found that BBPS segment scores of 2 or 3 (with 2 being noninferior to 3) was indicative of adequate bowel preparation for detection of adenomas > 5 mm, and for repeat colonoscopy at standard, guideline-recommended intervals (both parameters are USMSTFCC-recommended criteria for bowel preparation adequacy)[ 11 , 57 ].…”
Section: Validated Bowel Preparation Scalesmentioning
confidence: 99%
“…BBPS scores correlates with polyp detection rates and caecal intubation time 5,8. Lower BBPS score is associated with missed polyp detection and requires early repeat colonoscopy as it has negative impact on colon cancer prevention 6,9…”
Section: Introductionmentioning
confidence: 99%